Can Photodynamic Therapy Be an Alternative Method in Melanoma Treatment? - Choromańska, Anna; Kulbacka, Julita; Chwiłkowska, Agnieszka; Skołucka, Nina; Gamian, Andrzej; Saczko, Jolanta (IntechOpen, 2011)
None